2019
DOI: 10.1038/s41467-019-08387-8
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotency and X chromosome dynamics revealed in pig pre-gastrulating embryos by single cell analysis

Abstract: High-resolution molecular programmes delineating the cellular foundations of mammalian embryogenesis have emerged recently. Similar analysis of human embryos is limited to pre-implantation stages, since early post-implantation embryos are largely inaccessible. Notwithstanding, we previously suggested conserved principles of pig and human early development. For further insight on pluripotent states and lineage delineation, we analysed pig embryos at single cell resolution. Here we show progressive segregation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
166
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(203 citation statements)
references
References 66 publications
34
166
0
3
Order By: Relevance
“…Then, we identified differentially expressed genes (DGEs) between ICM and TE, and a total of 2080 DGEs were found ( Figure 3C; Table S4). 17 Consistent with a recent report, 15,23 increased expression of GATA3 and GATA2 was observed in TE. 17 Consistent with a recent report, 15,23 increased expression of GATA3 and GATA2 was observed in TE.…”
Section: Segregation Of Icm and Te In Porcine Ebsupporting
confidence: 91%
See 4 more Smart Citations
“…Then, we identified differentially expressed genes (DGEs) between ICM and TE, and a total of 2080 DGEs were found ( Figure 3C; Table S4). 17 Consistent with a recent report, 15,23 increased expression of GATA3 and GATA2 was observed in TE. 17 Consistent with a recent report, 15,23 increased expression of GATA3 and GATA2 was observed in TE.…”
Section: Segregation Of Icm and Te In Porcine Ebsupporting
confidence: 91%
“…15 In the study, we found that the overall expression trend of core and naïve pluripotent markers reported in mice and humans was high in the cells ( Figure 4A), confirming the signature of naïve pluripotency in porcine morula and ICM of EB. 15 In the study, we found that the overall expression trend of core and naïve pluripotent markers reported in mice and humans was high in the cells ( Figure 4A), confirming the signature of naïve pluripotency in porcine morula and ICM of EB.…”
Section: Emergence Of Pluripotency In Porcine Early Embryossupporting
confidence: 72%
See 3 more Smart Citations